Philippine Agriculture: Its Path to Modernization - Cristina C. David (Philippine Institute for Development Studies (PIDS), 1995)
Philippine agriculture has performed poorly despite its performance being relatively better than other Asian countries. This paper argues that misguided and inadequate government policies and programs have contributed to the erosion of the country's competitive advantage in the sector. Several of these problems can be found on major crops such as direct market interventions, import bans and hectarage limitation
Keywords: 330; uniform tariff rate